HR involvement in corporate governance - Supangco, Vivien T. (2006)
This study examined the relationship between the involvement of the human resource management function in formulating corporate governance mechanisms and the quality of their implementation. It also looked at the relationship between the quality of implementation of corporate governance mechanisms and performance. Of interest were two governance mechanisms : strategic plan elements and behavioral control practices. This study was based agency theory, institutional theory, and the resource-based view of the firm. The results revealed that quality of implementation resulted in higher performance. Specifically, quality of implementation of strategic plan elements not only explained performance but also served as an important enabler of quality of implementation of behavioral control policies. The importance of HR involvement, however, was realized in its impact on quality of implementation.